2021
DOI: 10.1002/essoar.10506514.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blue Flashes as Counterparts to Narrow Bipolar Events: the Optical Signal of Shallow In-Cloud Discharges

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Research results through the last 40 years indicate that, in addition to lightning, kilometer scale corona electrical discharges formed by hundreds of millions of streamers (Cooray et al., 2020; Li et al., 2021; N. Liu et al., 2019) are common in thunderclouds around the globe but their genesis (Le Vine, 1980; Neubert et al., 2021; Rison et al., 2016; Smith et al., 1999; Soler et al., 2020; Tilles et al., 2019), dynamics (Bandara et al., 2019, 2021; Jacobson & Heavner, 2005; Jacobson et al., 2013; Wiens et al., 2008) and probable atmospheric chemistry impact (Bozem et al., 2014; Gordillo‐Vázquez & Pérez‐Invernón, 2021; Minschwaner et al., 2008; Pérez‐Invernón et al., 2019; Shlanta & Moore, 1972; Simek, 2002; Zahn et al., 2002) remain to be well understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research results through the last 40 years indicate that, in addition to lightning, kilometer scale corona electrical discharges formed by hundreds of millions of streamers (Cooray et al., 2020; Li et al., 2021; N. Liu et al., 2019) are common in thunderclouds around the globe but their genesis (Le Vine, 1980; Neubert et al., 2021; Rison et al., 2016; Smith et al., 1999; Soler et al., 2020; Tilles et al., 2019), dynamics (Bandara et al., 2019, 2021; Jacobson & Heavner, 2005; Jacobson et al., 2013; Wiens et al., 2008) and probable atmospheric chemistry impact (Bozem et al., 2014; Gordillo‐Vázquez & Pérez‐Invernón, 2021; Minschwaner et al., 2008; Pérez‐Invernón et al., 2019; Shlanta & Moore, 1972; Simek, 2002; Zahn et al., 2002) remain to be well understood.…”
Section: Discussionmentioning
confidence: 99%
“…As presented in the introduction, based on what it is known about optical emissions of leaders and streamer coronas (Li et al., 2021; Neubert et al., 2021; Soler et al., 2020), and of MMIA photometer sensitivity and noise levels (Chanrion et al., 2019), an algorithm for identification of BLUEs was designed. The algorithm analyzed all the 337 nm/4 nm (blue) and 777.4 nm/5 nm (red) photometer events recorded by MMIA in the period of study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…
Thunderclouds occasionally penetrate into the stratosphere, forcing the exchange of air masses between the troposphere and the stratosphere 1,2 . Observations from space have shown that blue corona discharges are often generated in such thundercloud tops 3,4,5,6 and are the optical manifestation of so-called Narrow Bipolar Events (NBEs) observed in radio signals 7,8,9 . They come with two polarities, the positive that brings net negative charge aloft, and the negative that brings negative charge towards the earth.
…”
mentioning
confidence: 99%